Posisi daya saing perusahaan taksi Blue Bird pada era teknologi disruptif - Agustinus, Victor (Universitas Tarumanagara, 2017)
The number of internet users in Indonesia is increasing significantly. In Indonesia, the internet is not only accessed by PCs but also by smartphones. Therefore, new companies with new business models that utilize the internet-connected smartphone are popping up nowadays. Those newcomers are serious threats to existing companies. That phenomenon is called disruptive technology. It happens to all industries including taxi services. Today, conventional taxi companies are challenged by online taxi companies. This research is aimed at identifying the competitive position of conventional taxi companies in the macro and microenvironment.